The Application of Cognitive Ergonomics in Improving Observation Skills and Curiosity in Elementary Schools - Sumianto, Sumianto; Hanafi, Yusuf; Nusantara, Toto; Mardhatillah, Mardhatillah; Atmoko, Adi; Daulay, Musnar Indra; Yenni Fitra Surya (Universitas PGRI Yogyakarta, 2025)
Observation skills and curiosity are crucial for elementary students’ learning, but remain underdeveloped in Indonesia, where PISA (2021) reported that 56% of students struggle to identify key information in texts. This quasi-experimental study involved 80 fourth-grade students, divided into two groups: experimental and control. Over four weeks, the experimental group received lessons that integrated Dual Coding (text-image pairing and color-coded diagrams) and Chunking (breaking content into small, thematic units)—a 25-item, validated test measured both skills. Results from independent t-tests showed significant improvements (p < 0.05) across all indicators, with an average score increase of 18% in the experimental group. These findings confirm that structured multimodal strategies enhance visual-verbal processing, analytical thinking, and exploratory motivation. Practically, the study suggests that primary school curricula should incorporate cognitively ergonomic techniques to foster deeper engagement and higher-order thinking, offering a replicable model for inclusive and practical instructional design. Keywords: cognitive ergonomics, dual coding, chunking, observation skills, curiosity